KENDALA PERIZINAN PENANAMAN MODAL ASING DI INDONESIA - Andika Wahyu Wibowo; Ida Bagus Rai Djaja (Kertha Negara : Journal Ilmu Hukum, 2013)
To getting the good Indonesian economical, required the existence of investmentactivities, one of them is foreign investment. Implemation of Investment in Indonesia,unrarely have their own problems, such as related to licenses. The investor often tocomplaining about the unefficiency and lack of the facilities on the birocration licencesmanagement. The publication of Act No. twenty five of 2007 about the invesment does notnecessarily provide ease in handling licencing and the other handling.